Proximal Horizontal Flap Tears of TFCC Diagnosed by Computed Tomography Arthrography: Six Case Series - Arimitsu, Sayuri; Masatomi, Takashi; Shigi, Atsuo; Yukioka, Chikako; Moritomo, Hisao (Journal of Wrist Surgery, 2020)
Background Proximal horizontal tears of the triangular fibrocartilage complex (TFCC) represent the tears at the proximal surface of the articular disk with a normal appearance of the distal surface. Preoperative diagnosis of TFCC flap tears is challenging.Objectives This report aims to present a diagnostic method using computed tomography (CT) arthrography for the proximal horizontal flap tears of the TFCC and to report our clinical outcomes.Patients and Methods Six patients were included who were preoperatively suspected to have proximal horizontal flap tears of the TFCC via CT arthrography. Arthrography was conducted by injecting dye into the distal radioulnar joint (DRUJ), and CT images were obtained immediately following arthrography. We performed arthroscopic or direct flap debridement with concomitant surgeries: ulnar shortening with positive ulnar variance and corrective osteotomy with the malunion following distal radius fracture.Results Preoperative CT arthrography clearly revealed the flaps to be flipped over toward the radiopalmar side of the DRUJ in four cases and a teardrop-shaped dye defect in two. We were able to identify the dislocated flap by arthroscopy avulsed from the proximal aspect of the articular disk within the DRUJ in all six cases. The mean pain level decreased from 10 preoperatively to 0.3 postoperatively on the visual analog scale. The mean patient-rated wrist evaluation score decreased from 43.5 preoperatively to 11.2 postoperatively.Conclusions Our study shows that CT arthrography can be a promising method for diagnosing proximal horizontal flap tears of the TFCC. Debridement of the flaps and concomitant surgeries showed satisfactory clinical results.Level of Evidence This is a Level 4, diagnostic study.
Keywords: proximal; horizontal; flap tears; TFCC; CT arthrography